2014
DOI: 10.3109/01612840.2013.873103
|View full text |Cite
|
Sign up to set email alerts
|

Nearly Invisible: The Psychosocial and Health Needs of Women with Male Partners in Prison

Abstract: Very little research has been conducted investigating the health status and social needs of women with incarcerated male partners, despite the large number of men from underserved communities who are currently incarcerated. Research with women who have incarcerated male partners has primarily focused on communicable disease risk and family interactions. Women with incarcerated partners are often mothering children who are at risk for early and repeated incarceration, behavioral problems, and poverty. Gaining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A growing number of studies shows that caring for a recently incarcerated family member is stress inducing and can negatively affect one's mental and physical health (Cooke, 2014; Grieb et al, 2014; Kampfner, 1995; Murray & Farrington, 2008). More than half of respondents reported that their mental and/or physical health had worsened as a result of their relative's incarceration and/or reentry.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A growing number of studies shows that caring for a recently incarcerated family member is stress inducing and can negatively affect one's mental and physical health (Cooke, 2014; Grieb et al, 2014; Kampfner, 1995; Murray & Farrington, 2008). More than half of respondents reported that their mental and/or physical health had worsened as a result of their relative's incarceration and/or reentry.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, when taken together, the themes creating physical distance, indifference, and self-preservation suggest that family members who lacked social support resort to these coping mechanisms in an attempt to reduce the emotional and mental burden of caring for a recently incarcerated family member. Also related to prior literature was the theme avoiding social stigma (Arditti, 2005;Arditti, Lambert-Shute, et al, 2003;Cooke, 2014;Lee et al, 2014;Murray & Farrington, 2008). As the literature review described, family members experience stigma associated with their relative's incarceration, and this can have a detrimental effect on their social support networks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations